Reflections on criminal law and its teaching in Peru - Abanto Vásquez, Manuel (2024)
In criminal law, there is a serious crisis that has been generated not only by the influence of ideological conflicts in political field, but also by the limited capacity of the legislator to evaluate our reality before introducing foreign legislative tendencies.These in many cases, generate confusion and hinder the search for effective solutions.In this context, JD. Manuel Abanto shares his reflections based on his extensive professional experience and valuable academic contributions.He shares that criminal law faces multiple challenges, highlighting among them its excessive use as the first defense mechanism against all the evils of Peruvian society.